Retrofitting Digital Twins of Existing Systems - Fett, Michel; Macko, Stanislav; Wilking, Fabian; Götz, Stefan; Wartzack, Sandro; Kirchner, Eckhard (2024 IEEE International Symposium on Systems Engineering (ISSE), 2024)
Digital Twins offer a wide range of potentials in an industrial context but are rarely used in practice. Small and medium-sized companies in particular face challenges that can only be overcome with great effort and risk. One of these challenges is the fact that the development of Digital Twins is a complex and interdisciplinary task, for which small and medium-sized companies can rarely provide the necessary resources. Another challenge is that tight budgets lead to equipment and systems being used for a longer time and often do not provide the necessary elements for the use of Digital Twins. Therefore, this article presents an approach for retrofitting existing systems for Digital Twins by considering its three domains: models, sensors and IT infrastructure. The results are illustrated using a case stud